1004. PHILCOXIA RHIZOMATOSA: Plantaginaceae: Gratioleae. (11th October 2021) - Scatigna, André V.; Fleischmann, Andreas S.
Summary: Philcoxia rhizomatosa is a highly specialised carnivorous perennial herb endemic to the deep, white quartzite sand pans of the campos rupestres vegetation of eastern Brazil's Espinhaço Range, specifically within the northern portion of the range in the state of Minas Gerais. Philcoxia is among the most threatened genera of carnivorous plants and thus far all attempts to cultivate them have failed.